TARADUF DALAM AL-QUR’AN LAFADZ KAYD DAN KHIDA’: Identifikasi Ayat-Ayat al-Qur’an Yang Mengandung Kata Kayd dan Khida’,Konotasi makna kayd dan khida’ dalam Al-Qur’an,Persamaan dan perbedaan makna kayd dan khid’ah dalam Al-Qur’an - Annisa Mawaddah; Ibnu Arbi Tarigan (SOSIOEDUKASI, 2026)
This thesis is entitled "TARADUF IN THE QUR'AN: THE WORDS KAYD AND KHIDA'". In discussing the meaning of deception, the Qur'an uses several words, including the words kayd and khida'. The writing of this thesis aims to reveal the similarities and differences of the words kayd and khida' by analyzing interpretations in classical and contemporary books. The method applied in this research is library research which is qualitative in nature, using descriptive analytic method. The results of the research: (1) interpretations of the words kayd and khida' in the Qur'an according to the commentators: Sayyid Qutb explains in his interpretation that the term kayd refers to covert efforts to achieve a goal, which usually has negative or evil connotations. Wahbah al-Zuhaili mentions that "Khida'" comes from a root word meaning harm. This term refers to the act of deceit commonly done by hypocrites. (2) similarities and differences between the words kayd and khida': Literally, both of these words are interpreted as deception and considered as taraduf. Although considered as taraduf, these two words certainly have slight differences. The word kayd is understood as a form of someone's hidden deception with the intention of achieving a specific goal. This deceptive act involves planning, where the plan is already made before its execution. This kayd act can harm others. Although in the Qur'an there are perpetrators of kayd actions that are positive, this action is more often depicted in a negative form. Meanwhile, khida’ reflects the action of hiding the truth or presenting oneself differently from what is actually true. Therefore, perpetrators of khida' are difficult to predict, whether as friends or foes. This action can occur without planning. Keywords: Taraduf, Kayd and Khida'